The Fair Value Measurement of Biological Assets, Disclosure of Biological Assets and Financial Performance: The Moderating Effect of Managerial Ownership - Warsini Warsini; Ika Sasti Ferina; Relasari Relasari (Eduvest - Journal of Universal Studies, 2024)
This research aims to investigate the impact of the measurement and disclosure of biological assets on financial performance, and how this relationship is moderated by managerial ownership. Using signaling and agency theory as the theory as the theoretical foundation, the study used a sample size of 22 agricultural companies listed on the Indonesia Stock Exchange (IDX), with an observation period of 2019-2022. Panel data regression analysis was used in the study with a quantitative descriptive approach. The results show that the measurement of biological assets measured by fair value has a significant positive effect on financial performance. Other result shows an insignificant relationship between biological assets disclosure and financial performance. Regarding the moderating effect, the results demonstrate that managerial ownership significant moderating effect on the relationship between the measurement of biological assets and financial performance; meanwhile managerial ownership insignificant moderating effect on the relationship between biological assets disclosure and financial performance.